IMPROVING SPEAKING SKILL OF THE ELEVEN GRADE SMA NEGERI 7 PALU THROUGH THINK-PAIR-SHARE TECHNIQUE - Olivia, Zetrin; Munir, Syahrul; Mashuri, Mashuri (Tadulako University, 2024)
This research aims to find out was think pair share can improve students’ speaking skill of Eleven Grade at SMA Negeri 7 Palu or not. The instrument used to collect the data was speaking test. The students in this research were divided into two groups which are experimental and control group. 30 sudents from each group were asked to do pre-test and post-test. The students speaking skill were analyzed by use rubric score adapted from Weigle (2002). Then, the data were analyzed using formula proposed by Arikunto (2013). The result shows that the t-counted is 9.65 and t-table is 2.00 where the t-counted was higher than the t-table. It indicates that the think pair share technique can improve students’ speaking skill of Eleven Grade at SMA Negeri 7 Palu.